Motivasi Pengunjung Melakukan Leisure and Recreation di Daya Tari Wisata Malioboro, Yogyakarta - Widiandari, Ni Komang Otami Astuti; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i01.p20, 2021)
Shopping center Malioboro offers a variety of souvenirs typical of Yogyakarta such as shirts, batik, blankon, sandals, and various types of handicrafts. In addition, Malioboro also serves as a culinary center with stalls along the street serving typical food and beverages at very cheap prices. Malioboro also has old buildings of Dutch colonial heritage. This research is located at Jalan Malioboro, Sosromenduran, Gedong Tengen, Yogyakarta City, Special region of Yogyakarta. The aims of this research to understand the attraction, accessibility, amenities, and ancillary also the tourist motivations in this tourist destination. The accidental sampling technique using for informants to collecting data. This research uses qualitative methods with techniques of observation, interview, questionaire, and documentation study. The data analysist technique used descriptive qualitative analysis. The research finds that many variety of attractions (culinary, shopping tour, building architecture, and street artists), accesibility (by transportation and information), amenities (hotels and tourism support facilities) and ancillary (UPT and merchant associations) existed in Malioboro. The motivation of visitors divided by two factors that is the push factor (out of saturation and curiosity) and pull factor (images owned, cheap prices provided, and the atmosphere offered by Malioboro). Keywords: Tourist Motivations, Leisure and Recreation, Malioboro